Finance and Democracy in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
This paper focuses on how political regimes affect financial development in Africa, contingent on religious-domination, income-levels and colonial-legacies. The main findings are summarized as follows. Authoritarian regimes have a higher propensity to effect policies that favour the development of financial intermediary depth, activity and size. Democracy has important effects on the degree of competition for public offices but less significant effects in comparison with autocracy on policies towards financial development. As a policy implication, once democracy is initiated, it should be accelerated (to edge the appeals of authoritarian regimes) and reap the benefits of level and time hypotheses in financial development.
Keywords: E40; E50; O10; P16; P50; 330; Banking; Finance; Politics; Democracy; Development